A Spatial Analysis of Subgrade Density Value of Cisumdawu Hihgway (KM 10+700 – 12+000) - Fauzi, Ihwan; Susanto, Eri (Universitas Pendidikan Indonesia, 2019)
Uniformity of subgrade density value is very necessary, including in Cisumdawu highway. Spatial analysis with geostatistical computation was applied to predict and map subgrade density value. Geostatistical method used was kriging method based on semivariogram model. The data collected were a sandcone test from 2 zones of dry density value at last layer of compaction. Results of spatial measurements showed that existing values have spatial correlation with diversity influenced by distance and type of distribution, also direction of data distribution from subsgrade density. Zone 1 reached level of compatibility of 99.5% and Zone 2 of 99.4%. Mapping value of subgrade density was influenced by normal data distribution, distance between samples and spread pattern. Selection of semivariogram model showed standard deviation value in zone 1 of 0.0025 and zone 2 of 0.004, it indicates accuracy could meet confidence level of 95%. This result was expected to provide accurate evaluation of subgrade compaction work.